The effect of plyometric training on power and kicking distance in female adolescent soccer players - Rubley, M. D.; Haase, A. C.; Holcomb, W. R.; Girouard, T. J.; Tandy, R. D. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to measure the effects of low-frequency, low-impact plyometric training on vertical jump (VJ) and kicking distance in female adolescent soccer players. Sixteen adolescent soccer players were studied (age 13.4 ± 0.5 years) across 14 weeks. The control group (general soccer training only) had 6 subjects, and the plyometric training (general soccer training plus plyometric exercise) group had 10 subjects. All subjects were tested for VJ and kicking distance on 3 occasions: pre-test, 7 weeks, and 14 weeks. Data were analyzed using a 2 (Training) × 3 (Test) analysis of variance (ANOVA) with repeated measures on the factor test. No significant difference in kicking distance was found between groups at pre-test (p = 0.688) or 7 weeks (p = 0.117). The plyometric group had significantly greater kicking distance after 14 weeks (p < 0.001). No significant difference in VJ height was found between groups at pre-test (p = 0.837) or 7 weeks (p = 0.108). The plyometric group had a significantly higher VJ after 14 weeks (p = 0.014). These results provide strength coaches with a safe and effective alternative to high-intensity plyometric training. Based on these findings, to increase lower-body power resulting in increased VJ and kicking distance, strength coaches should implement once-weekly, low-impact plyometric training programs with their adolescent athletes.